The Illusions on Digital Citizenship: What We Know and What We Do? - ÖZDENER DÖNMEZ, NESRİN (My University, 2021)
Introduction: The purpose of this paper is to examine the relationship between the digital citizenship levels of information and communication technology teacher candidates and their user behaviours and habits in the digital world. The experimental work presented here provides one of the first investigations into a deeper understanding of misconceptions, problems, and deficiencies in digital citizenship and its sub-dimensions. Also, the study offers some important insights to bring solutions to the problems encountered in teaching the concept to individuals. Methods: To reach the goal, a mixed-method approach was utilized. Participants of the study were 74 information and communication technology teacher candidates enrolling at a public university in Turkey. Data for this research were collected using Digital Citizenship Scale (Kocadağ, 2012) and the e-Citizen mobile application. A combination of quantitative and qualitative approaches was used in the data analysis. Results: According to the research findings, it was established that the participants did not have sufficient awareness of the concept of digital citizenship in the sub-dimensions of digital security, digital health, digital rights and responsibilities, digital law, digital etiquette, and digital commerce. The digital citizenship levels of the participants in these dimensions obtained from the scale were not consistent with their digital technology user behaviours and habits. Considering digital access, digital communication, and digital literacy sub-dimensions, it was concluded that pre-service teachers had sufficient knowledge. Another research finding shows that the responses of the participants to the scales should be questioned and emphasizes the importance of using different data collection methods. Discussion: It was specified that the average digital citizenship score of 74 information and communication technology teacher candidates participated in the study was found to be 262 and it was described as “Very Good.” These results corroborate with the findings of a great deal of the previous works that show that digital citizenship levels of individuals have increased in recent years. However, data obtained from user habits and behaviours did not support this situation. This inconsistency may be due to the participants not acting objectively during scale scoring. The reason for this is not clear, but we thought possible causes maybe that teacher candidates may not express their real thoughts, may not want to get low scores on Digital Citizenship Scale (DCs) or they may see themselves as adequate despite their deficiencies. This situation is one of the biggest limitations of self-report measures and it is named “Social Desirability Bias” in the literature. There are, however, other possible explanations. In the study, participants have filled the DCs first and then used the e-Citizen application. Information and communication technology teacher candidates have taken lower scores from User Habits and Behaviours Surveys (UHBs) in each of the sub-dimensions compared to DCs. According to these data, we can infer that the participants may be able to increase their knowledge about digital citizenship and see their deficiencies thanks to the e-Citizen mobile application. Limitations: It should not be forgotten that this study was limited by the validity and reliability of the digital citizenship scale, the efficiency of the mobile application, and the level of knowledge of the participant group and their objectivity in their answers. Conclusion: Overall, this study strengthens the idea that there are problems in the concept of digital citizenship and its sub-dimension. As a result of the research, although the digital citizenship levels of the participants were measured to be very good, it was determined that there are inconsistencies with their behaviours and habits during the use of digital technologies in six of the nine sub-dimensions (security, health, rights and responsibilities, law, etiquette, and commerce). In three subdimensions: digital communication, access, and literacy, the data were relatively consistent. At the end of the study, the possible causes of the digital citizenship misconception experienced by teacher candidates were discussed separately and suggestions were made for future studies. Key words: digital citizenship, e-Citizen, mobile application.
Keywords: digital citizenship; e-Citizen; mobile application